Literature Review: The Effectiveness of Giving Ginger (Zingiber Officinale Roscoe) to Pregnant Women Nausea Vomiting 1st Trimester Pregnancy - Mahayu Ciptaning Mulia; Catur Leny Wulandari (Green Publisher Indonesia, 2021)
Nausea and vomiting often occur when you wake up in the morning, which is also called morning sickness. Nausea and vomiting that occur in the first trimester of pregnancy are caused by increased levels of the hormone Estrogen and Human Chorionic Gonadotropine (HCG) in serum from the placenta and can cause a decrease in appetite so that there is a change in electrolyte balance with potassium, calcium and sodium which causes changes in body metabolism. Nausea and vomiting during pregnancy affects about 80-90% of pregnant women. Ginger (Zingiber officinale Roscoe) is the most widely used herbal therapy in the management of nausea and vomiting. The purpose of this study was to determine how effectiveness ginger was in reducing the frequency of nuesea and vomiting in pregnant women in the 1st trimester.This study uses a literature study method obtained through electronic media with keywords. There were 8 selected articles, consisting of 5 international and 3 national articles. This article provides information about the effectiveness of giving ginger to reduce the frequency of nausea and vomiting in pregnant women in the 1st trimester. The conclusions obtained from the analysis are that ginger can reduce nausea and vomiting in pregnant women in the 1st trimester.